2018
DOI: 10.6035/2174-0992.2018.15.8
|View full text |Cite
|
Sign up to set email alerts
|

Info-show in European television: searching for the social engagement of the audience

Abstract: Desde la invención de la televisión, el acto de visionado siempre ha tenido vinculado un componente social, pasando a convertirse en un agente socializador al que se le asocia una actividad de condición colectiva. Este aspecto se ha visto acrecentado de forma marcada en los últimos años desde la aparición y popularización de los smartphones y las redes sociales. Estos nuevos dispositivos han conseguido extender las posibilidades sociales vinculadas a la televisión, llevando, entre otras cuestiones, a la transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…This research supports the results of recent work in which it is observed that the social audience does not behave as creatively, actively, and interactively as might be expected (Lin & Chiang, 2019;Rodríguez et al, 2017), in this sense, no political consequences were perceived given the low activity of the social audience. In the same way, in the action of the profiles of the programmes examined, inconsistent and not very innovative production, promotion, and communication strategies are also observed (Coromina et al, 2020;Franquet et al, 2018;Sequera, 2013). These actions are not adapted to the platform's characteristics, and the resources it offers are not used productively, nor is engaging content created to generate a greater interaction with users.…”
Section: Discussionmentioning
confidence: 77%
“…This research supports the results of recent work in which it is observed that the social audience does not behave as creatively, actively, and interactively as might be expected (Lin & Chiang, 2019;Rodríguez et al, 2017), in this sense, no political consequences were perceived given the low activity of the social audience. In the same way, in the action of the profiles of the programmes examined, inconsistent and not very innovative production, promotion, and communication strategies are also observed (Coromina et al, 2020;Franquet et al, 2018;Sequera, 2013). These actions are not adapted to the platform's characteristics, and the resources it offers are not used productively, nor is engaging content created to generate a greater interaction with users.…”
Section: Discussionmentioning
confidence: 77%
“…Real-time conversations allow viewers to use this platform while watching linear television. This activity has promoted a change in the behaviour of audiences, feeding the concept of prosumers (Toffler, 1980;Jenkins, 2006;García-Galera & Valdivia, 2014) and enhancing the increasingly active role of audiovisual consumption (Franquet et al, 2018).…”
Section: Television and Social Media Imagesmentioning
confidence: 99%
“…Previous studies have already noted on the interest of The Voice for the study of social television due to their methods of promoting the linear programme on social media and blending of social media platforms with the use of official hashtags, the presence of users messages on screen or the posting of tweets by the broadcaster, the profile of the programme and other people related to the talent show such as the host, the judges or the contestants (Ellis, 2014;Franquet, et al, 2018;van Es, 2016;Yao, 2017).…”
Section: Television and Social Media Imagesmentioning
confidence: 99%
See 1 more Smart Citation
“…La información se ha ido trivializando y toda pieza informativa es interesante para ser mostrada al espectador. Surge el nuevo concepto de «hipervisibilidad», relativo a la posibilidad de consumir información alcanzable mediante la mirada (i- Calvet et al, 2018). Según Imbert (1999, p. 6), este nuevo concepto se define como «una hipertrofia visual: un mostrar todo, de manera recurrente y al modo espectacular, con una tendencia a la dramatización».…”
Section: Estado De La Cuestiónunclassified